Kontekstualisasi Situs-Situs Megalitik di Pegunungan Muria Jawa Tengah, Dalam Sistem Kepercayaan Kejawen (Kajian Etnoarkeologi) - , ANDHIKA ARIEF DRAJAT PRIYATNO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Topic The finding of megalithic tradition sites on Muria Mountains is apparently interesting to examine, since people still using those sites for Kejawen ritual. Though the sites were found scattered into a few location, it is still connected to each other. There is a modification to the sites in shape and influence from another beliefs as Hindu-Budha and Islam, but still with an obvious concept of ancient cult. Then the question that appear is about the context of those megalithic sites present days. Problems and Objectives The question of this research is âHow the contextualization of megalithic sites of Muria Mountains in the Kejawen belief system?â The objective of this research is to know the context of megalithic sites on present days, especially in the Kejawen belief system. To complete the objective, the writer need to assemble the data about religion development in the south side of Muria Mountains area. Methods Inductive approach was used in this research, with deep descriptive which is giving the archaeological data through the etnographical work system. Then artefactual analysis is done with artefact and environment as the variable, also analysis of symbol with the stage of the exegesical meaning, operational and positional approach. The result of analysis was synthesised and the conclusion appear so the quaestion of the research can be answered. Conclusion The megalithic tadition sites that had been found were related to the cult ritual. The utilizing of site that continues has made the modification and interference of belief that developed in Indonesia. Syncretism between megalithic tradition, Hindu- Budha and Islam has showed up a site context in Javanese traditional belief or it called Kejawen that can be seen on the sites in Muria Mountains.